Grieving the death of a pet: coping strategies from Quran and Hadith - Versay Kudus, Nazima (Academy of Language Studies, 2022)
Introduction Losing a pet can be very upsetting and one of the hardest things to go through. A pet is a beloved family member who provides companionship, fun, and joy to our lives. Yet, when faced with its death, it can be overwhelming for family members. Many articles were written by the West on the coping strategies that can be adopted. However, one article that appears in the Mufti Wilayah Persekutuan’s website catches my attention the most. An enquirer wrote to the Mufti asking, “Is it possible to see my beloved cat once again in paradise? The Mufti responded citing verses from the Quran and hadiths. Obligation towards all creatures Narrated by Syaddad bin Aus RA: The Prophet said PBUH said: “Verily Allah has prescribed ihsan (proficiency, perfection) in all things.” In another hadith, narration from Abdullah bin ‘Umar RA where the Prophet PBUH said: "A woman was tortured and was put in Hell because of a cat which she had kept locked till it died of hunger." Allah's Messenger (iS)further said, (Allah knows better) Allah said (to the woman), 'You neither fed it nor watered when you locked it up, nor did you set it free to eat the vermin of the earth (Sahih al-Bukhari 2365). In the first hadith, Muslims are instructed to treat all of Allah SWT's creatures kindly. This involves being kind to all hu-man beings and also showing compassion for animals. Thus it is compulsory to have ihsan or mercy towards animals. In the second hadith, we learned that it is against the shariah and haram to oppress or treat them badly. Additionally, failing to take care of them may result in someone being punished in Hellfire.